A pair potential modeling study of F3− in neon matrices. Issue 2 (21st December 2020) - Bader, Frederik; Tremblay, Jean Christophe; Paulus, Beate
Abstract : First-principles investigations of the trifluoride anion in a neon environment reveal a small blue-shift of the fundamental vibrational excitations. Abstract : In this study, the structural and vibrational properties of a trifluoride anion trapped in solid neon are investigated. For that, a potential energy surface based on a truncated many-body expansion scheme is constructed from explicitly correlated coupled cluster calculations. Cluster modeling and minima hopping optimizations are used to evaluate different neon environments, revealing a dominant underlying structural motif in the guest–host system. Moreover, vibrational analyses of the trapped trifluoride anion are performed. These show the subtle ways in which the neon matrix affects the vibrational properties of the trifluoride. In particular, the vibrational states are slightly compressed and fundamental transitions are blue-shifted within the matrix. Also, the calculated vibrational transition energies are in quantitative agreement with available experimental observations, validating the employed procedure for future applications.